Sedimentological and bacterial paleontological peculiarity of the vivianite phosphorites in the Zavkhan basin, Western Mongolia - Dorjnamjaa, Dorj; Enkhbaatar, Batkhuyag; Altanshagai, Gundsambuu (Mongolian Journal of Paleontology, 2021)
Discovery of the Ediacaran – Lower Cambrian Zavkhan phosphate basin in the western Mongolia was an impetus to investigating distribution of the bedded phosphorites in car-bonate and detritus formations of the shelf framework. The Zavkhan phosphate basin has been discovered by us as a result of many years’ standing scientific investigation. This basin locates in the west of Mongolia within the territory of Zavkhan and Gobi-Altai provinces inclusive 24000 km2 of space. In this basin phosphate or stone of fertility was accumulated approximately 635-500 mya. The geologic history of the basin gives a possibility to correlate with 80 world phosphate basins. The phosphate-bearing sediments in the Ediacaran-Lower Cambrian Tsagaanolom and Bayangol formations have been described. The structure and lithological composition of the Zavkhan phosphate sedimentation are well-known to be essentially similar to the phosphate sediments of the main part of the Khubsugul and Karatau phosphate basins. In lithology and bio-geochemistry, the Tsagaanolom carbonate formation is distinctly subdivided into underlying phosphate, vivianite phosphate and overlying phosphate members. The Tsagaanolom and Bayangol formations are characterized by heterogeneous cyanobacterial mat, including zoo-benthos, zoo-plankton and phytogenic organisms. Bayangol Formation mainly consists of detritus sediments and aluminous and stony or collophanitic (Ca3P2O8·2H2O) black meta-phosphate rock with pyritic gold, silver-bearing mineralization of sulfosalt type.